KOMNAS HAM'S HUMAN RIGHTS JURISDICTION OVER BUSINESSES INVOLVED IN THE HAZE CRISIS - Prinhandono, Iman; Hosen, Nadirsyah; Boom, Kelly (Indonesia Law Review, 2021)
Indonesia’s forest fires have caused a serious haze problem nationally and in the Southeast Asian region, which has caused harm to the rights to life, health and a healthy environment, work, education, and many others. The forest fires largely stem from harmful slash-and-burn methods of land clearing, done at large scales by corporations. Judicial mechanisms have proven ineffective to deter violating corporations and bring justice to victims. From a legal standpoint, Komnas HAM’s quasi-jurisdictional powers allow it to act as a non-judicial grievance mechanism for victims in the haze crisis and against violating corporations. However, issues with the non-binding nature of its reports and mediation, inability to compel violating corporations to participate in its investigation and mediation, as well as declining trust in Komnas HAM’s integrity may prove to be significant barriers to the effective exercise of jurisdiction and the provision of effective remedies to victims. Komnas HAM and ELSAM’s national human rights plan, issued in 2017, is a step in the right direction. However, further steps are required from a legislative standpoint to broaden Komnas HAM’s mandate for it to effectively perform its functions, in the haze crisis and beyond.